2017
DOI: 10.1021/acs.nanolett.7b04183
|View full text |Cite
|
Sign up to set email alerts
|

Atom Transfer Radical Polymerization of Multishelled Cationic Corona for the Systemic Delivery of siRNA

Abstract: We propose an effective siRNA delivery system by preparing poly(DAMA-HEMA)-multilayered gold nanoparticles using multiple surface-initiated atom transfer radical polymerization processes. The polymeric multilayer structure is characterized by transmission electron microscopy, matrix-associated laser desorption/ionization time-of-flight mass spectrometry, UV-vis spectroscopy, Fourier transform infrared spectroscopy, dynamic light scattering, and ζ-potential. The amount of siRNA electrostatically incorporated in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 81 publications
1
31
0
Order By: Relevance
“…The organic polymer layer covering the metallic core of the gold nanoparticles leads to the creation of hybrid materials, which can be used as a molecular diagnostic tool as well as element of the drug delivery system, hence the wide interest in the modification of such nanoparticles exhibiting high application ability in biomedical fields. It is worth noting that intensified research on the modification of gold nanoparticles in recent years effected in simple modifications [63] through a core–shell structure of gold NPs [64] or even advanced biomedical applications such as the SiRNA delivery system reported in 2018 [52].…”
Section: Gold Nanoparticlesmentioning
confidence: 99%
See 1 more Smart Citation
“…The organic polymer layer covering the metallic core of the gold nanoparticles leads to the creation of hybrid materials, which can be used as a molecular diagnostic tool as well as element of the drug delivery system, hence the wide interest in the modification of such nanoparticles exhibiting high application ability in biomedical fields. It is worth noting that intensified research on the modification of gold nanoparticles in recent years effected in simple modifications [63] through a core–shell structure of gold NPs [64] or even advanced biomedical applications such as the SiRNA delivery system reported in 2018 [52].…”
Section: Gold Nanoparticlesmentioning
confidence: 99%
“…The ability to synthesize polymer brushes on the surface of nanoparticles (e.g., gold (Au) [51,52], silver (Ag) [53], silica (Si) [35,54], titanium (Ti) [55], cobalt (Co) [56], and zinc (Zn) [39]) via the SI-ATRP approach provides efficient tool that can be applied in a wide range of engineering applications such as a membrane technology [57] as well as biomedical applications [56,58,59,60] including immunotherapy [61] and antifouling surfaces [62].…”
Section: Introductionmentioning
confidence: 99%
“…Since gold nanoparticles (AuNPs) possess well-defined localized surface plasmon resonance (LSPR) bands in the UV–near infrared (IR) regions, they are commonly used in surface-enhanced Raman scattering (SERS) for improved diagnostic imaging [ 1 , 2 , 3 ] and in photothermal ablation of tumors [ 4 , 5 , 6 ]. Recently, AuNPs have been widely utilized in innovatively therapeutic strategies on various cancers [ 7 , 8 , 9 ]. Saha et al reported that gold nanoparticle reprograms pancreatic tumor microenvironment and inhibits tumor growth [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…AuNPs can be stabilized by a large variety of stabilizers like polymers, ligands, biomolecules, denrimers, surfactants, etc. ; 84 , 101 , 102 , 103 , 104 the stabilizers affect not only the relative instability and aggregation but also cell uptake and toxicity, which points to the necessity of strategic engineering of NPs surface chemistry. 105 , 106 , 107 Gu and colleagues 108 developed a novel AuNP beacon by optimizing the sequence amount, and they modified PEG and cell-penetrating peptide (CPP) on the gold core ( Figure 5 ).…”
Section: Main Textmentioning
confidence: 99%